FEASIBILITY STUDY OF WOOD WORKSHOP SPACES CONTRUCTION AND PROPERTY BUSINESS EXPERTISE STUDY AT STATE VOCATIONAL SCHOOL 1 PALANGKA RAYA - Sabar Hasudungan Pandiangan; Lola Cassiophea (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
The purpose of this study was to determine the feasibility of the wood workshop space, wood workshop lighting system, and woodworking furniture and equipment at SMK N 1 Palangka Raya based on the standards required by Permendiknas No. 40 of 2008 and SNI 03-6575-2001. This is done to provide convenience and feasibility for users. The results of this study are (1) the wood workspace area of SMK N 1 Palangka Raya does not meet the standard with an area of 198 m² which is smaller than the standard of 256 m² with an achievement percentage of 77.34%, the area of the equipment storage room and the wood workshop instructor room has meet the standard with an area of 72 m² larger than the standard of 48 m² with an achievement percentage of 150%, the overall area of the wood workshop does not meet the standard with an area of 270 m² smaller than the standard of 304 m² with an achievement percentage of 88.8%. (2) The level of lighting in the wood workshop room at SMK N 1 Palangka Raya has not met the standard, namely min 500 lux with a lighting level of 400 lux in the morning with an achievement percentage of 80%, during the day 411 lux with an achievement percentage of 82%, in the afternoon day of 408 lux with an achievement percentage of 81%. (3) Equipment and furniture for the wood workshop room at SMK N 1 Palangka Raya, single station equipment does not meet the standard with the number of equipment that meets the standard is 1 type of tool and 20 types of tools that meet the standard with a size of achievement of 4.76%, equipment double station there are 3 types of tools that meet the standards and 9 types of tools that do not meet the standards with a size of 16.66% standard achievement, workshop furniture there are 3 types of furniture that do not meet the standards and 4 types of furniture that meet the standards with a large standard achievement are 42.85%.